School Heads’ Leadership Skills and Attitudes as Determinants of School-Community Partnership - Varona, Fe C. (JPAIR Institutional Research, 2017)
This study employed a descriptive-correlational research design focused mainly on exploring the relationship between the extent of school-community partnership and the school heads’ leadership skills and attitudes towards school-community partnership. Respondents of the study include the nine (9) school heads, 101 teachers, 90 parents, and 56 local officials of Butuan City, Philippines. Results showed that the school heads exhibit satisfactory leadership skills and highly positive attitudes towards school-community partnerships. Moreover, there is a very high extent of partnership between the school and community in the conduct of school events. Additionally, the school heads’ leadership skills and attitudes towards school-community partnerships both have significant, direct, and moderate relationships with the extent of school-community partnerships.